ACADEMIC PROCRASTINATION AND ITS RELATIONSHIP WITH SCHOOL ANXIETY IN HIGH SCHOOL STUDENTS FROM ORELLANA - Elizabeth Sarango Chillo; Catherine Shugulí (PSICOLOGÍA UNEMI, 2023)
Abstract: Academic procrastination has become a frequent problem in the wake of the COVID-19 pandemic. This behavioral pattern, which can negatively affect academic performance and adolescents' subjective well-being perception, has not been thoroughly studied in the Latin American context. The aim of this study was to analyze the relationship between academic procrastination and school anxiety in students from an educational unit in the province of Orellana, Ecuador. The quantitative methodology with a non-experimental cross-sectional design and correlational scope was used to study a sample of 210 students from the General Unified Baccalaureate, with a mean age of M = 15.93 years. The results indicate that students present low levels of Academic Procrastination and moderate levels of School Anxiety, with a significant but mild correlation (r = 0.208; p = 0.002) between the two variables. These findings are relevant to better understand academic procrastination and its implications in the region, and it is expected to encourage future studies in Ecuador. Additionally, they can be useful in designing strategies and programs aimed at reducing academic procrastination and school anxiety in this student population.